Construction of covered walkway at Jalan Hang Jebat infrastructure at PNB 118, Kuala Lumpur / Muhammad Zulfadzli Shamsulanizam - Shamsulanizam, Muhammad Zulfadzli (Universiti Teknologi MARA UiTM,Perak, 2022)
A Covered Walkway is a passage or path for people to walk along. Walkway can be constructed two ways either Precast Walkway or In-Situ Walkway. Walkway is an important thing that has been constructed and around the world has walkway. Walkway is really useful for pedestrians and additional Covered Walkway will make the walkway become more useful which will put mindset for pedestrians that this is the walkway that can give they shelter from bad circumstances such as raining. Construction of Covered Walkway types Aluminium were constructed along Rezab Jalan Hang Jebat to Rezab Jalan Galloway, Infrastructure Work at PNB118, Kuala Lumpur. Aim of this report was to shows how the Construction of Covered Walkway types Aluminium were constructed. Not only that, this report will show the most dangerous problems that can be found during Excavation Work. Method that has been used during construction work was necessary as it defined the efficiency of the working progress of the construction.